PENGARUH PENAMBAHAN TEPUNG DAGING IKAN NILA TERHADAP TINGKAT KESUKAAN KUE TELUR GABUS - Anggreini, Diyah Ayu; Junianto, Junianto; Rostika, Rita; Rostini, Iis (Universitas Mataram, 2025)
Increasing the protein content in Cork Egg Cake can be done by adding tilapia meat flour. This study aims to determine the best percentage of tilapia meat flour addition in making cork egg cake to produce the most preferred product and determine the proximate composition or nutritional profile of the most preferred cork egg cake product. The method used is an experimental method, namely making cork egg cake with different levels of tilapia meat flour addition, consisting of four treatments (0%; 7.5%; 10%; and 12.5%) with 20 semi-trained panelists as replicates to determine the level of panelist preference for cork egg cake. The parameters observed were hedonic test and chemical test. The most preferred addition of tilapia meat flour to the cork egg cake was the 10% treatment with an average value of appearance 8.4; texture 7.8; aroma 7.8; taste 8.1. The resulting proximate test is 3.90% moisture content; 1.56% ash content; 8.52% protein content; 26.21% fat content; and 59.81% carbohydrate content. Key words: Fish Meat Flour, Cork Egg Cake, Favorability, Proximate Test